The Hercules Mixer Volume 4, Number 5 (Hercules Incorporated, 1922)
May 1922 issue of The Hercules Mixer, the Hercules Powder Company's in-house publication that provided both historical and technical information and also offered a glimpse of employees' day-to-day lives at the company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry--Periodicals; Employees; Explosives industry; Periodicals; Chemical industry; Corporations; Hercules Powder Company; Hercules Incorporated